Higher vascular plant abundance associated with decreased ecosystem respiration after 20 years of warming in the forest-tundra ecotone - Myrsky, Eero; Mikola, Juha; Kaarlejärvi, Elina; Olofsson, Johan; Sjögersten, Sofie; Tupek, Boris; Männistö, Minna K.; Stark, Sari (Wiley-Blackwell, 2024)
1. The on-going climate warming is promoting shrub abundance in high latitudes, but the effect of this phenomenon on ecosystem functioning is expected to depend on whether deciduous or evergreen species increase in response to warming. 2. To explore effects of long-term warming on shrubs and further on ecosystem functioning, we analysed vegetation and ecosystem CO2 exchange after 20 years of warming in the forest–tundra ecotone in subarctic Sweden. A previous study conducted 9 years earlier had found increased evergreen Empetrum nigrum ssp. hermaphroditum in the forest and increased deciduous Betula nana in the tundra. 3. Following current understanding, we expected continued increase in shrub abundance that would be stronger in tundra than in forest. We expected warming to increase ecosystem respiration (Re) and gross primary productivity (GPP), with a greater increase in Re in tundra due to increased deciduous shrub abundance, leading to a less negative net ecosystem exchange and reduced ecosystem C sink strength. 4. As predicted, vascular plant abundances were higher in the warmed plots with a stronger response in tundra than in forest. However, whereas B. nana had increased in abundance since the last survey, E. hermaphroditum abundance had declined due to several moth and rodent outbreaks during the past decade. In contrast to predictions, Re was significantly lower in the warmed plots irrespective of habitat, and GPP increased marginally only in the forest. The lower Re and a higher GPP under warming in the forest together led to increased net C sink. Re was negatively associated with the total vascular plant abundance. 5. Our results highlight the importance of disturbance regimes for vegetation responses to warming. Climate warming may promote species with both a high capacity to grow under warmer conditions and a resilience towards herbivore outbreaks. Negative correlation between Re and total vascular plant abundance further indicate that the indirect impacts of increased plants on soil microclimate may become increasingly important for ecosystem CO2 exchange in the long run, which adds to the different mechanisms that link warming and CO2 fluxes in northern ecosystems.
Keywords: arctic greening; climate changes; CO2 exchange; deciduous shrubs; evergreen shrubs; moth outbreaks